Methicillin-Resistant Staphylococcus aureus Colonization among Health Care Workers in a Downtown Emergency Department in Toronto, Ontario - Gregory Saito; Jessica Thom; Yanliang Wei; Piraveina Gnanasuntharam; Pirasanya Gnanasuntharam; Nathan Kreiswirth; Barbara Willey; Michelle Loftus; Catherine Varner; Vanessa Porter; Allison McGeer; Bjug Borgundvaag (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: Methicillin-resistant Staphylococcus aureus (MRSA) acquired in the community, otherwise known as community-acquired MRSA, has emerged rapidly in recent years. Colonization with MRSA has been associated with an increased risk of symptomatic and serious infections and, in some settings, health care workers (HCWs) exhibit a higher prevalence of MRSA colonization.